The H1N1 Influenza Pandemic: A Review of Recent Experience (Bangladesh Medical Journal, 2010)
The world has recently experienced a pandemic caused by a novel virus named H1N1. This antigenetically shifted virus spread to 213 countries through human to human transmission. In Bangladesh 899 cases were occurred. Therefore, a proper and clear insight is urgently required to prevent an outbreak in the future and make preparations that may be planned well in advance. This review is an attempt to discuss the historical perspective of the swine flu virus, its epidemiology and route of transmission to better understand the various control measures that may be taken to fight the danger of another global pandemic. Key words: H1N1; Pandemic DOI: 10.3329/bmj.v39i1.6231 Bangladesh Medical Journal 2010; 39(1): 31-39